Inserção dos atores subnacionais no processo de integração regional: o caso do Mercosul - Prado, Henrique Sartori de Almeida (2010)
This dissertation deals with the subject "The insertion of subnational actors in the process of regional integration: the case of MERCOSUL." This study aims to examine the involvement of subnational actors in the process of regional integration, through the paradiplomacy, based on the integrative experience of the Southern area of South America. The research deals with the historical development, characteristics and development of the regional integration process and outlines a comparative study on the constitutional limitations of foreign participation of subnational entities of Member States of MERCOSUL. Finally, this work describes the experiences of subnational integration within MERCOSUL and the concern to justify the action of these actors in the international sphere.